The Unmet Needs of People with Chronic Obstructive Pulmonary Disease: A Systematic Review of Qualitative Findings. (2nd January 2018) - Clari, Marco; Ivziku, Dhurata; Casciaro, Riccardo; Matarese, Maria
ABSTRACT: The complexity of chronic obstructive pulmonary disease (COPD) can negatively impact the lives of people with the condition and compromise their capacity to take care of their needs. Unmet needs can then lead to significant morbidity, unpleasant emotional experiences and a poor quality of life; thus this systematic review aimed to identify, evaluate and synthesise the qualitative literature on the unmet needs of people with COPD. A qualitative meta-synthesis was performed according to the Joanna Briggs Institute method. A systematic search of five databases was conducted, searching for articles published from January 1995 to May 2017. Eight papers were identified. Two researchers extracted the data and independently assessed their quality. The total sample of people with COPD included was 108. Nine categories were derived from 49 findings, and aggregated into three synthesised findings: (1) people with COPD have unmet needs regarding information about the disease; (2) people with COPD have unmet physical, emotional and social needs, due to the disease symptoms and treatments; and (3) people with COPD have unmet care needs. This review showed qualitative evidence regarding the dimensions in which people with COPD express their unmet needs. The needs that are mainly unsatisfied include physical, psychosocial, informational and practical aspects, as well as the need for healthcare professional care. A global approach, which includes the areas identified by our findings, could lead to an improvement in the care of people with COPD and could improve the self-care management of those individuals who do not correctly identify their needs.